Observations on Samuel Davies - Davies, Samuel, 1723-1761.
Volume (39 pages) of observations on Samuel Davies.
Clergyman and college president.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Clergy; College presidents